The aspects of constitutional anthropology in medicine (Eurasian Journal of Ecology, 2016)
The paper proposes to use achievement constitutional anthropology in medicine. Predetermination of certain diseases, depending on the body type can carry out preventive measures: such as the creation of special groups separated by the type of constitution.
Keywords: anthropology; the type of constitution; prevention